The Viking and the runaway Empress - Rodi, Sarah (Harlequin historicals., 2024)
Bound by duty, tempted by desire. Guard to the Byzantine emperor, Viking warrior Destin is tasked with delivering his sovereign's runaway bride-to-be to Constantinople. Abandoned at birth, Destin has spent years making something of himself, and with this final task comes the promise of land and riches. Only, the fiercely beautiful Livia refuses to be wed! Destin must return her unharmed--and untouched--but the closer they grow on their journey, the harder it becomes for him to hand her over...